Irish Nationalism in Canada - Wilson, David A (McGill-Queen's studies in ethnic history, 2009)
The nine contributors in this book argue otherwise - and in doing so make a major and original contribution to our understanding of the Irish experience in Canada and the place of Irish-Canadian nationalism within an international context. Focusing on the period 1820 to 1920, they examine political, religious, and cultural expressions of Irish-Canadian nationalism as it responded to Irish events and Canadian politics. They also look at tensions within the movement between those who argued that Ireland should share the same freedom that Canada enjoyed within the British Empire and revolutionary republicans who wanted to liberate both Ireland and Canada from the yoke of British imperialism.